Principles and applications of fermentation technology - Kuila, Arindam; Sharma, Vinay (Wiley, 2018)
The book covers all aspects of fermentation technology such as principles, reaction kinetics, scaling up of processes, and applications. The 20 chapters written by subject matter experts are divided into two parts: Principles and Applications. In the first part subjects covered include: -Modelling and kinetics of fermentation technology -Sterilization techniques used in fermentation processes -Design and types of bioreactors used in fermentation technology -Recent advances and future prospect of fermentation technology The second part subjects covered include: -Lactic acid and ethanol production using fermentation technology -Various industrial value-added product biosynthesis using fermentation technology -Microbial cyp450 production and its industrial application -Polyunsaturated fatty acid production through solid state fermentation -Application of oleaginous yeast for lignocellulosic biomass based single cell oil production -Utilization of micro-algal biomass for bioethanol production -Poly-lactide production from lactic acid through fermentation technology -Bacterial cellulose and its potential impact on industrial applications.